Fracture Mechanics Inverse Problems and Solutions - Bui, Huy Duong. (Solid Mechanics and Its Applications,, 2006)
This book is an outgrowth of my involvement in two groups of research in solid mechanics, created in 1960 for the French nuclear energy program. At this time, it was decided that France, as a no-oil reservoir country, must be powered by nuclear energy, which represents today 80% of the total - tional energy supply. Long before the construction of the first nuclear plant at Fessenheim in 1973, Electricité de France (EdF) created its first solid mechanics laboratory, appointed researchers and sent them to the universities or abroad in order to learn about theories and new methods of assessment of the safety of structures. Working at EdF, I was training in Professor Jean Mandel’s laboratory at Ecole Polytechnique (LMS), Paris. My friend René Labbens, working at Framatome (the builder of nuclear plants) was training at the Lehigh University, under the guidance of professors G. R. Irwin and G. C. Sih. We had to work hard, both academically at the u- versities laboratories and performing engineering tasks for our employer. This dual position was a great chance for many of us, since we discovered that real industrial problems are the source of new subjects and research problems to be solved by theoreticians in the universities and conversely we immediately knew if our theoretical work was good or not for appli- tions as revealed in our daily works conducted for our industrial employer.